Gambaran Pengetahuan Menggosok Gigi dengan Kejadian Karies Gigi Pada Anak-Anak Pemulung - Dominikus Suryo Skukubun; Firman Firman; Zilal Islamy Paramma; Ayu Wulandari (Jurnal Terapi Gigi dan Mulut, 2025)
Data from the Indonesian Ministry of Health indicate that the majority of the population brushes their teeth daily (94.7%). However, only 2.8% practice toothbrushing at the recommended times, namely after breakfast and before going to bed. The Basic Health Research (Riskesdas) also reports a high prevalence of dental caries among children, reaching 81.1% in those aged 3–4 years, 92.6% in children aged 5–9 years, and 73.4% among those aged 10–14 years. This study aimed to describe toothbrushing knowledge and its relationship with the occurrence of dental caries among scavenger children at the Makassar City landfill site. A descriptive study design was employed, involving a population of 75 scavenger children aged 6–12 years. Total sampling was applied, meaning all eligible children were included as respondents. Data were analyzed using SPSS through descriptive statistical analysis (univariate) and cross-tabulation (bivariate). The results showed that most respondents had a good level of toothbrushing knowledge (53.3%), while 25.3% had moderate knowledge and 21.3% had low knowledge. Furthermore, dental caries were found in the majority of children (94.7%), whereas only 5.3% were free from caries.